Health literacy and the Affordable Care Act: a policy analysis for children with special health care needs in the USA - Keim-Malpass J; Letzkus LC; Kennedy C (Dove Medical Press, 2015)
Jessica Keim-Malpass,1 Lisa C Letzkus,1,2 Christine Kennedy1 1University of Virginia School of Nursing, 2University of Virginia Children’s Hospital, Charlottesville, VA, USA Abstract: Children with special health care needs (CSHCN) represent populations with chronic health conditions that are often high utilizers of health care. Limited health literacy has emerged as a key indicator of adverse health outcomes, and CSHCN from limited health literacy families are particularly vulnerable. The purpose of this policy analysis is to outline key provisions in the Affordable Care Act (ACA) that incorporate health literacy approaches for implementation and have implications for CSHCN in the USA. Several key provisions are incorporated in the ACA that involve health literacy and have implications for CSHCN. These include: expansion of public insurance coverage and simplifying the enrollment process, provisions assuring equity in health care and communication among all populations, improving access to patient-centered medical homes that can offer care coordination, ensuring enhanced medication safety by changing liquid medication labeling requirements, and provisions to train health care providers on literacy issues. More research is needed to determine how provisions pertaining to health literacy in the ACA are implemented in various states. Keywords: children, special health care needs, health literacy, Affordable Care Act, health policy